2023
DOI: 10.1101/2023.10.06.561316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic analyses of Asiatic Mouflon in Iran provide insights into the domestication and evolution of sheep

Dong-Feng Wang,
Pablo Orozco-terWengel,
Meng-Hua Li
et al.

Abstract: The wild ancestor of domestic sheep, Asiatic mouflon (O. gmelini), consists of several subspecies mainly distributed in Iran nowadays. However, the impact of the Asiatic mouflon subspecies in Iran on sheep domestication remains unclear. Here, we conducted a comprehensive population genomics analysis of Asiatic mouflons in Iran with 780 whole-genome sequences, 767 whole mitogenomes, and 239 Y chromosomes. Whole-genome sequence analyses revealed two subpopulations of the Asiatic mouflons in Iran:O. gmelini_2 lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
(156 reference statements)
1
2
0
Order By: Relevance
“…Previous work reported that ASM was the wild sheep lineage genetically closest to DOM, relative to other wild sheep, implying that ASM could have been the wild source of domestic sheep [42][43][44][45]. Here we found that ANM and CYM cluster with EUM and DOM, with ASM as outgroup, a pattern supported by MDS, f 3 and f 4 statistics.…”
Section: Phylogenetic Relationships Between Anatolian and Cyprian Mou...supporting
confidence: 80%
“…Previous work reported that ASM was the wild sheep lineage genetically closest to DOM, relative to other wild sheep, implying that ASM could have been the wild source of domestic sheep [42][43][44][45]. Here we found that ANM and CYM cluster with EUM and DOM, with ASM as outgroup, a pattern supported by MDS, f 3 and f 4 statistics.…”
Section: Phylogenetic Relationships Between Anatolian and Cyprian Mou...supporting
confidence: 80%
“…Previous work reported that the ASM from Iran was the wild sheep lineage genetically closest to DOM, relative to other wild sheep, implying that ASM could have been the wild source of DOM ( Hiendleder et al 2002 ; Chessa et al 2009 ; Cheng et al 2023 ; Wang et al 2023 ). Here, we report that ANM and CYM cluster with EUM and DOM, with ASM as outgroup, a pattern supported by MDS and f 3 and f 4 statistics.…”
Section: Discussionmentioning
confidence: 99%
“…The ASM ( Ovis gmelini ; formerly Ovis orientalis ) is currently represented by three to five subspecies ranging through Armenia, Iraq, Iran, Turkey, and Cyprus ( Garel et al 2022 ). This group is considered to include the closest living relatives of the wild source population of DOM ( Hiendleder et al 2002 ; Chessa et al 2009 ; Cheng et al 2023 ; Wang et al 2023 ). The ASM is listed as “Near Threatened” under the IUCN Red List criteria as of 2024, with most populations numbering in the thousands.…”
Section: Introductionmentioning
confidence: 99%